1989
DOI: 10.1210/jcem-69-4-729
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Atrial Natriuretic Peptide Gene in Human Fetal Heart*

Abstract: Expression of the human atrial natriuretic peptide (hANP) gene was examined in tissues of 19 to 28-week-old human fetuses. As expected the fetal atria express the hANP gene at a high level, accruing substantial quantities of ANP immunoreactivity and ANP mRNA. The neonatal ventricle also expresses the hANP gene at a significant level. ANP mRNA levels in the ventricle were, on the average, about 20% of those in the right atria. ANP immunoreactivity in ventricle was less that 5% of that in the right atria, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…ANP granules, similar to those in atria, have been found within human foetal ventricles (Gardner et al, 1989) and neonatal rat ventricles (Thompson et al, 1986). The expression of the ANP gene decreases rapidly after birth and remains low, and often undetectable, in normal adult ventricles .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…ANP granules, similar to those in atria, have been found within human foetal ventricles (Gardner et al, 1989) and neonatal rat ventricles (Thompson et al, 1986). The expression of the ANP gene decreases rapidly after birth and remains low, and often undetectable, in normal adult ventricles .…”
Section: Discussionmentioning
confidence: 82%
“…Several recent studies have demonstrated that rat (Bloch et al, 1986;Wei et al, 1987;Wu et al, 1988) and human (Tsuchimochi et al, 1988;Gardner et al, 1989) ventricular myocytes can synthesize ANP during the very early neonatal or foetal periods. ANP granules, similar to those in atria, have been found within human foetal ventricles (Gardner et al, 1989) and neonatal rat ventricles (Thompson et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have documented that ventricular myocardium expresses relatively high levels of ANF during embryonic development and in the neonatal period (55)(56)(57)(58)(59). Shortly after birth, the expression of the ANF gene in the ventricle is downregulated, resulting in restricted expression of the ANF gene primarily to the atria.…”
Section: Resultsmentioning
confidence: 99%
“…Neonates with a CVP score ≤ 6 had significantly higher NT-proANP levels than had those with higher CVP scores. NT-proANP levels reflect distention of the fetal cardiac chambers and correlate with increased venous pressure 15,22 . Accordingly, we found that fetuses with umbilical venous pulsations demonstrated significantly higher NT-proANP levels than did fetuses with nonpulsatile umbilical venous flow.…”
Section: Discussionmentioning
confidence: 99%